Framework of business and information technology alignment - Rukmana, Otong; Mulyono, Nur Budi (2010)
Business and Information Technology (IT) alignment is a critical key succes factors for IT role to achieve business goals. Various approaches have not provided specific and structured process to align business and IT.This research develop a framework of process oriented-business and IT alignment through adaptation of Strategic Alignment Model (SAM), Strategic Business-IT Alignment (SBITA), model of vertical and horizontal alignment, and model of alignment maturity assessment. The framework consists of four alignment process, they are” integrate strategy”,”cascade strategy”, “integrate operation”, and “evaluate alignment”, with maturity measure of six criteria and its attributes. This will provide clear and structured processes in aligning business and IT.